Restricted and repetitive behaviors and association with cognition and adaptive functioning in children with autism spectrum disorder in Singapore - Lin, Wanyun; Chan, Yiong Huak; Kiing, Jennifer S. H.; Lim, Tammy S. H.; Chong, Shang Chee; Kang, Ying Qi; Aishworiya, Ramkumar; Mulay, Kalyani Vijayakumar; Tan, Mae Yue (Frontiers in Psychiatry, 2023)
Background One of the core features of autism spectrum disorder (ASD) is restricted, repetitive patterns of behavior, interests and activities (RRBs). RRBs are known to adversely affect cognition and adaptive functioning. We explored the relationship of RRBs with cognition and adaptive functioning in children with ASD in an Asian setting. Methods This cross-sectional study was conducted at a tertiary developmental pediatrics center in Singapore from September 2019 to October 2021. Parent-child dyads (parents and their children ≤7 years old diagnosed with ASD) were recruited. Parents completed the Repetitive Behavior Questionnaire-2 (RBQ-2), which reports total score and two subscales – Motor/Sensory Behaviors (RBQ-2 MS) and Rigidity/Routines/Preoccupation with Restricted Interests (RBQ-2 RRPRI). Standardized assessments included Mullen Scales of Early Learning (MSEL) and Vineland Adaptive Behavior Scales (VABS-II). Data analysis utilized descriptive statistics and Pearson’s correlation. Results Parents of 113 children [75.2% male, mean (SD) age 5.0 (1.2) years] participated. Median (IQR) RBQ-2 score was 29.0 (11.0). Significant negative correlations (adjusted for age, gender and family history of ASD) were observed for total RBQ-2 scores with MSEL ELC scores (r = −0.248, n = 101, p = 0.014) and VABS-II ABC scores (r = −0.281, n = 88, p = 0.009). Specifically, these correlations of fair strength were seen only with the RBQ-2 MS subscale for both ELC (r = −0.321, n = 101, p = 0.001) and ABC (r = −0.3478, n = 88, p = 0.001). Conclusion In children with ASD, severity of RRBs correlated with adverse cognition and adaptive functioning measures in our study, consistent with Western literature. While our study does not show causality, it adds to literature serving as a foundation for further research for both clinicians and researchers to target RRBs in improving outcomes with children in ASD.